Comparison of Tubal Sterilization Procedures Performed by Keyless Abdominal Rope-Lifting Surgery and Conventional CO2 Laparoscopy: A Case Controlled Clinical Study - Kahraman Ülker; Ürfettin Hüseyinoğlu (The Scientific World Journal)
Objective. To evaluate the safety and efficacy of Keyless Abdominal Rope-Lifting Surgery (KARS), for tubal sterilization procedures in comparison with the conventional CO2 laparoscopy. Material and Methods. During a one-year period, 71 women underwent tubal ligation surgery. Conventional laparoscopy (N=38) and KARS (N=33) were used for tubal sterilization. In KARS, an abdominal access pathway through a single intra-abdominal incision was used to place transabdominal sutures that elevated the abdominal wall, and the operations were performed through the intraumbilical entry without the use of trocars. In CO2 laparoscopy, following the creation of the CO2 pneumoperitoneum a 10 mm trocar and two 5 mm trocars were introduced into the abdominal cavity. Tubal sterilizations were performed following the creation of the abdominal access pathways in both groups. The groups were compared with each other. Results. All operations could be performed by KARS without conversion to CO2 laparoscopy or laparotomy. The mean operative time of the two groups was not significantly different (P>0.05). Intra- and postoperative findings including complications, bleeding, and hospital stay time did not differ between groups (P>0.05). Conclusion. KARS for tubal sterilization seems safe and effective in terms of cosmesis, postoperative pain, and early hospital discharge.